Gêneros textuais em jogos digitais - Cajueiro, Luiz Eduardo Cerquinho (2014)
This research introduces a classification model for digital games, based upon the textual genre theory. The motivation is to forge a common ground for dialog between the many disciplines that study the digital games, like Information Sciences, Social Sciences, Communication and Art Studies, including as well the game developers community. The epistemic basis for this work are the genre theories by Bakthin (1979), Charaudeau (1997) and Marcuschi (2003, 2004, 2008), the studies in multimodality and hypermodality by Kress e Van Leeuwen (1996) and Braga (2004, 2005), the communication theories by Lévy (1993, 1996, 2000, 2001) and David Crystal (apud Shepherd, Saliés, 2013) and theories in digital game studies presented by Crawford (1984), Wolf (2001, 2003), Aarseth et al. (2003) and Branco (2011). The digital games genre classification system proposed in this work is different from the previously proposed, since it accounts for the discursive locus it identifies, and the possibility of including any digital game. The conclusion was that it is possible to distinguish, in digital games, the thematic, stylistic, formal and discursive obrigatory characteristics for the creation of a textual genres classification, and it is possible to use a common lexic between the different areas of knowledge that access the digital games.